2022
DOI: 10.3390/cancers14071821
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on the Use of DNA Repair Inhibitors as a Tool for Imaging and Radionuclide Therapy of Glioblastoma

Abstract: Despite numerous innovative treatment strategies, the treatment of glioblastoma (GB) remains challenging. With the current state-of-the-art therapy, most GB patients succumb after about a year. In the evolution of personalized medicine, targeted radionuclide therapy (TRT) is gaining momentum, for example, to stratify patients based on specific biomarkers. One of these biomarkers is deficiencies in DNA damage repair (DDR), which give rise to genomic instability and cancer initiation. However, these deficiencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 284 publications
(483 reference statements)
0
4
0
Order By: Relevance
“…It can act as a single agent or in combination with other drugs, such as gemcitabine and cytarabine (NCT00779584). MK-8776 was previously known as SCH 900776, a pyrazolo[1,5-a]pyrimidine derivative that binds with the hinge region located in the kinase ATP-binding site [ 341 , 345 ]. Previous studies show that MK-8776 treatment can enhance cancer-cell sensitivity to hydroxyurea, gemcitabine, and radiation, leading to DNA damage accumulation [ 346 , 347 ].…”
Section: Dynamic Balance Between Kinases and Phosphatases In Dsbs Rep...mentioning
confidence: 99%
“…It can act as a single agent or in combination with other drugs, such as gemcitabine and cytarabine (NCT00779584). MK-8776 was previously known as SCH 900776, a pyrazolo[1,5-a]pyrimidine derivative that binds with the hinge region located in the kinase ATP-binding site [ 341 , 345 ]. Previous studies show that MK-8776 treatment can enhance cancer-cell sensitivity to hydroxyurea, gemcitabine, and radiation, leading to DNA damage accumulation [ 346 , 347 ].…”
Section: Dynamic Balance Between Kinases and Phosphatases In Dsbs Rep...mentioning
confidence: 99%
“…PARP1-mediated PARylation is sufficient for oligodendrocyte progenitor cell differentiation ( 53 ), and PARP1 polymorphisms was regarded as one of the potential risk factors for spinal cord injury (SCI) in a clinical study ( 54 ). Besides, brain or spinal cord tumors remain difficult types of cancers to treat, such as glioblastoma (GBM), even after four PARP inhibitors were approved by FDA as PARP1 overexpression is present in various cancers ( 55 ). For other diseases that are resulted from structural damage of the nervous system, such as Bell's palsy, carpal tunnel syndrome, cervical spondylosis, Guillain-Barré syndrome, and peripheral neuropathy, PARP affects neuronal recovery albeit no direct evidence exists to prove the exact roles of PARP in these pathological changes.…”
Section: Parp1 In Cns Diseasesmentioning
confidence: 99%
“…Since both, RT and chemotherapy induce DNA damage and activate DDR, molecules that target DDR inhibition are investigated for their therapeutic role in overcoming treatment resistance (Ref. 14). Surprisingly, even though the DDR pathway activates post-irradiation in both parent cells and recurrent cells, Kaur et al .…”
Section: Introductionmentioning
confidence: 99%
“…Since both, RT and chemotherapy induce DNA damage and activate DDR, molecules that target DDR inhibition are investigated for their therapeutic role in overcoming treatment resistance (Ref. 14). Surprisingly, even though the DDR pathway activates post-irradiation in both parent cells and recurrent cells, Kaur et al demonstrated on GBM cell line models (U87MG and SF268) that there are differences in the DDR pathway activation in primary versus recurrent post-treatment GBM cells.…”
Section: Introductionmentioning
confidence: 99%